Identifikasi Kerapatan Vegetasi dengan Algoritma Normalized Difference Vegetation Index (NDVI) di Kota Batu Jawa Timur - Nailufar, Balqis ; Syahadat , Ray March; Ameliawati , Presti (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2018)
This study aims to knows: 1) the density of vegetation (NDVI) using Landsat-8 OLI/TIRS (Operational Land Imager/Thermal Infrared Sensor). The data used in this research are  the data density of vegetation and an area that is tapped from Landsat imagery 8 OLI/TIRS (Operational Land Imager/Thermal Infrared Sensor) in 2018 years.  The method used in this study is the interpretation of Landsat 8 to calculate the density of vegetation index or diffrerence Normalized Vegetation Index (NDVI) obtained by calculation near infrared to red reflected by plants. Technical analysis using Geographic Information System (GIS) and remote sensing, to determine the value of the vegetation canopy density using the results of calculation of the NDVI, then value the NDVI class reclassified (reclass) into four classes, namely the density of sky or water, stone and open field, shrubs, and forest. Results of the study indicate are: 1) the density of vegetation in the study area with  class of clouds and water  has extensive 1,1 ha, Stone and open field an the area of 7416.1 Ha, bushes  has extensive 8552.0 Ha, and forest has extensive 3945.8 ha.